Optimal location of thyristor controlled series compensator using sensitivity approach [electronic resource] - New, Huang Chin, 1982- author; Mohd. Wazir Mustafa; Fakulti Kejuruteraan Elektrik (2014)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2014